Interesting Sum of Unity

Algebra Level 5

The polynomial P ( z ) z n + 1 1 P(z) \equiv z^{n+1}-1 has roots 1 , α , α 2 , α n 1,\alpha,\alpha^2 \ldots ,\alpha^n , where α \alpha is a complex ( n + 1 ) th (n+1)^{\text{th}} root of unity.

What is the value of 2 1 α + 2 1 α 2 + 2 1 α 3 + + 2 1 α n \dfrac{2}{1-\alpha}+\dfrac{2}{1-\alpha^2}+\dfrac{2}{1-\alpha^3}+\cdots+\dfrac{2}{1-\alpha^n} ?

n n n + 1 n+1 n 2 \frac{n}{2} 2 n 2n

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Jack Lam
Feb 23, 2016

Method 1: Polynomial Transformation \text{Method 1: Polynomial Transformation}

By the method of transformation, P ( 1 1 z ) P(1-\frac{1}{z}) has roots 1 1 α , 1 1 α 2 , 1 1 α 3 , , 1 1 α n \frac{1}{1-\alpha}, \frac{1}{1-\alpha^2}, \frac{1}{1-\alpha^3}, \cdots, \frac{1}{1-\alpha^n} .

P ( 1 1 z ) = ( 1 1 z ) n + 1 1 = 0 P(1-\frac{1}{z})= \left(1-\frac{1}{z} \right)^{n+1} -1 = 0 ( z 1 ) n + 1 z n + 1 = 0 \Rightarrow (z-1)^{n+1} -z^{n+1} =0

Expanding using the binomial theorem, the first three terms are:

z n + 1 + z n + 1 ( n + 1 ) z n + ( n + 1 ) n 2 z n 1 + -z^{n+1} + z^{n+1} -(n+1)z^n + \frac{(n+1)n}{2}z^{n-1} +\cdots

So the equation with the desired roots is:

( n + 1 ) z n + ( n + 1 ) n 2 z n 1 + = 0 -(n+1)z^n+\frac{(n+1)n}{2}z^{n-1} +\cdots =0

Using Vieta's Formulae, we have:

2 1 α + 2 1 α 2 + 2 1 α 3 + + 2 1 α n = 2 ( n + 1 ) n 2 ( n + 1 ) = n \frac{2}{1-\alpha}+\frac{2}{1-\alpha^2}+\frac{2}{1-\alpha^3}+\cdots+\frac{2}{1-\alpha^n} = -2\frac{\frac{(n+1)n}{2}}{-(n+1)} = n

Method 2: Careful Summation \text{Method 2: Careful Summation}

Consider the following result: 2 1 β + 2 1 1 β = 2 \frac{2}{1-\beta}+\frac{2}{1-\frac{1}{\beta}}=2

We also know α k α n + 1 k = 1 \alpha^k\alpha^{n+1-k} = 1

Summing up the terms pairwise from end to end, we have:

2 1 α + 2 1 α n = 2 , 2 1 α 2 + 2 1 α n 1 = 2 , \frac{2}{1-\alpha}+\frac{2}{1-\alpha^n}=2,\frac{2}{1-\alpha^2}+\frac{2}{1-\alpha^{n-1}}=2,\cdots

If n n is even, then all the terms pair perfectly and we are done. The resultant sum is equal to n n

If n n is odd, there is the root z = 1 z=-1 , whose transformation is just 1 1 and we are done. The resultant sum is also equal to n n .

Method 3: Calculus \text{Method 3: Calculus}

Consider the natural logarithm of P ( z ) P(z) . By the fundamental theorem of algebra, we have:

log ( z n + 1 1 ) = log ( z 1 ) + log ( z α ) + + log ( z α n ) \log{(z^{n+1}-1)}=\log{(z-1)}+\log{(z-\alpha)}+\cdots+\log{(z-\alpha^n)}

Differentiate both sides with respect to z z , giving us:

( n + 1 ) z n z n + 1 1 = 1 z 1 + 1 z α + 1 z α 2 + + 1 z α n \frac{(n+1)z^n}{z^{n+1}-1}=\frac{1}{z-1}+\frac{1}{z-\alpha}+\frac{1}{z-\alpha^2}+\cdots+\frac{1}{z-\alpha^n}

Subtract from both sides to place the common singularity of z = 1 z=1 on the left hand side.

( n + 1 ) z n z n + 1 1 1 z 1 = 1 z α + 1 z α 2 + + 1 z α n \frac{(n+1)z^n}{z^{n+1}-1}-\frac{1}{z-1}=\frac{1}{z-\alpha}+\frac{1}{z-\alpha^2}+\cdots+\frac{1}{z-\alpha^n}

n z n ( z n 1 + z n 2 + + z + 1 ) z n + 1 1 = 1 z α + 1 z α 2 + + 1 z α n \frac{nz^n - (z^{n-1}+z^{n-2}+\cdots+z+1)}{z^{n+1}-1} =\frac{1}{z-\alpha}+ \frac{1}{z-\alpha^2}+\cdots+\frac{1}{z-\alpha^n}

Take the limit as z 1 z \to 1 , allowing us to invoke L'Hôpital's rule. The limit can be directly applied to the sum without any problem.

2 1 α + 2 1 α 2 + 2 1 α 3 + + 2 1 α n = 2 lim z 1 n z n ( z n 1 + z n 2 + + z + 1 ) z n + 1 1 \frac{2}{1-\alpha}+\frac{2}{1-\alpha^2}+\frac{2}{1-\alpha^3}+\cdots+\frac{2}{1-\alpha^n} = 2\lim_{z \to 1} \frac{nz^n - (z^{n-1}+z^{n-2}+\cdots+z+1)}{z^{n+1}-1}

2 1 α + 2 1 α 2 + 2 1 α 3 + + 2 1 α n = 2 lim z 1 n 2 z n 1 ( ( n 1 ) z n 2 + ( n 2 ) z n 3 + + 2 z + 1 ) ( n + 1 ) z n \frac{2}{1-\alpha}+\frac{2}{1-\alpha^2}+\frac{2}{1-\alpha^3}+\cdots+\frac{2}{1-\alpha^n} = 2\lim_{z \to 1} \frac{n^2 z^{n-1} - ((n-1)z^{n-2}+(n-2)z^{n-3}+\cdots+2z+1)}{(n+1)z^n}

2 1 α + 2 1 α 2 + 2 1 α 3 + + 2 1 α n = 2 n 2 ( ( n 1 ) + ( n 2 ) + + 2 + 1 ) n + 1 \frac{2}{1-\alpha}+\frac{2}{1-\alpha^2}+\frac{2}{1-\alpha^3}+\cdots+\frac{2}{1-\alpha^n} = 2\frac{n^2 - ((n-1)+(n-2)+\cdots+2+1)}{n+1}

2 1 α + 2 1 α 2 + 2 1 α 3 + + 2 1 α n = 2 n 2 ( n 1 ) n 2 n + 1 = n 2 + n n + 1 = n \frac{2}{1-\alpha}+\frac{2}{1-\alpha^2}+\frac{2}{1-\alpha^3}+\cdots+\frac{2}{1-\alpha^n} = 2\frac{n^2 - \frac{(n-1)n}{2}}{n+1}=\frac{n^2+n}{n+1}=n

Can you explain why z=-1 when n is odd? Great solution.

Mateo Matijasevick - 5 years, 3 months ago

Log in to reply

Because if n is odd, n+1 is even, and for all even polynomials of unity, -1,1 are roots.

Jack Lam - 5 years, 3 months ago
Otto Bretscher
Feb 24, 2016

Let's do it like little Gauss, taking the sum twice and dividing by two: k = 1 n ( 1 1 α k + 1 1 α n + 1 k ) \sum_{k=1}^{n}(\frac{1}{1-\alpha^k}+\frac{1}{1-\alpha^{n+1-k}}) = k = 1 n 1 α n + 1 k + 1 α k 1 α k α n + 1 k + 1 = k = 1 n 1 = n =\sum_{k=1}^{n}\frac{1-\alpha^{n+1-k}+1-\alpha^k}{1-\alpha^k-\alpha^{n+1-k}+1}=\sum_{k=1}^{n}1=n . All we need is α k α n + 1 k = α n + 1 = 1 \alpha^k \alpha^{n+1-k}=\alpha^{n+1}=1 .

This is just a refinement of Jack's "Method 2", of course, without having to deal with the even/odd cases.

Vishesh Agarwal
Dec 12, 2018

@Jack Lam shouldn't in method 2 it be if n is odd then the terms perfectly match

Aaghaz Mahajan
Mar 24, 2018

Did it the same way as @Jack Lam (Method 1).....But for JEE Style, simply put n=1 and solve!!!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...